A Pengembangan Bahan Ajar Digital Berbasis Agama Dan Kearifan Local Sebagai Upaya Meningkatkan Kemampuan Berfikir Kreatif Siswa - Siti Seituni (Jurnal Penelitian Pendidikan, 2025)
This study aims to develop digital teaching materials based on religion and local wisdom to improve students' creative thinking skills at SMK AT-TAMIMI Situbondo. The study uses the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. A total of 14 grade X students were involved. Validation results from material and media experts averaged 90% (very feasible), and student responses reached 92% (very feasible). These findings suggest that the developed digital learning materials effectively enhance creativity while integrating cultural and religious contexts